URGENSI PENDIDIKAN MORAL DAN KARAKTER DALAM MEMBENTUK KEPRIBADIAN PESERTA DIDIK - Aprilina Wulandari; Agus Fauzi (Edupedia : Jurnal Studi Pendidikan dan Pedagogi Islam, 2021)
This article discusses the urgency of moral and character education in shaping the personality of students. Character is an important thing in a person's life, because character is one of the determinants of a person's success. Therefore, a strong and positive character needs to be well formed. Education not only aims to make students smart, but also must be able to create noble values ​​or character. Character building, especially students, is urgent and urgent to be realized in order to create a better society, namely a society that can face regional and global challenges. The regional and global challenge in question is how our young generation does not only have academic abilities that focus on cognitive abilities, but affective aspects and morality are also touched. The birth of moral and character education as an effort to revive the ideal-spiritual pedagogy that was lost by the wave of positivism. The substance of moral and character education is to form a complete personality for each student. The behaviors that are expected to be born are; do honesty, help people, respect, be responsible, appreciate, cherish, accept each other, sympathy, empathy, and accept what it is. Education as the totality of efforts and actions must be carried out through three educational institutions, namely, family, school and community. Therefore, it is necessary to integrate family education institutions, school education, and community education institutions in carrying out character education. The strengthening of the three educational institutions shows that character education is needed in order to anticipate future problems that are increasingly complex.